Investigation on the effect of abrasive waterjet parameter on machining stainless steel - Hafiz, Husin; Mohd Nazir, Mat Nawi; Gebremariam, M. A.; Azmir, Azhari (Springer, 2020)
Abrasive waterjet machining (AWJM) can perform various machining operations on almost any material including hard to machine materials. However, performance of a process depends on the chosen set of parameters. AWJM has major parameters such as traverse rate, water pressure, standoff distance and abrasive flowrate that will affect its performance. The present study investigates the effects of AWJM parameters (i.e. traverse rate, water pressure and standoff distance) on the width, depth and roughness of a channel produced at the surface of stainless steel. The results showed that by reducing the standoff distance and water pressure, the width of the channel was also reduced. For channel depth, increasing traverse rate produced a shallower channel depth. In contrast, increasing the water pressure produced a deeper channel depth. The surface roughness of the channel showed significant improvement by reducing the water pressure at a lower traverse speed and standoff distance. A proper selection of parameters is required in order to produce a suitable channel during AWJM surface texturing process.